Core Muscle Injuries: Preoperative Imaging and Postoperative Considerations - Couillard, Sherri; Adler, Blaire; Meyers, William C.; Zoga, Adam C.; Poor, Alexander E.; Kamel, Sarah I. (Seminars in Musculoskeletal Radiology, 2025)
Core muscle injuries constitute a significant source of pain and functional impairment among elite athletes. Understanding the anatomy and biomechanics centered at the pubic bone joint is necessary to interpret imaging findings. Dedicated athletic pubalgia magnetic resonance imaging (MRI) plays a crucial role in accurately diagnosing and assessing injuries affecting the pubic plate and associated muscular attachments. Preoperative findings can include harness muscle injury, pubic plate detachment, and/or osteitis pubis. Various surgical approaches are used for core muscle repair, requiring close collaboration with the referring surgeon during the interpretation of postoperative MRI. Although postoperative MRI can indicate healing progress, its primary usefulness lies in detecting new or exacerbated tears that may signify potential reinjury or surgical complications.
Keywords: athletic pubalgia; rectus abdominis; pubic plate; adductor origin; secondary cleft